Short-Term Dissolved Organic Carbon Dynamics Reflect Tidal, Water Management, and Precipitation Patterns in a Subtropical Estuary - Regier, Peter; Jaffé, Rudolf (Frontiers in Marine Science, 2016)
Estuaries significantly impact the global carbon cycle by regulating the exchange of organic matter, primarily in the form of dissolved organic carbon (DOC), between terrestrial and marine carbon pools. Estuarine DOC dynamics are complex as tides and other hydrological and climatic drivers can affect carbon fluxes on short and long time scales. While estuarine and coastal DOC dynamics have been well studied, variations on short time scales are less well constrained. Recent advancements in sonde technology enable autonomous in situ collection of high frequency DOC data using fluorescent dissolved organic matter (fDOM) as a proxy, dramatically improving our capacity to characterize rapid changes in DOC, even in remote ecosystems. This study utilizes high-frequency fDOM measurements to untangle rapid and complex hydrologic drivers of DOC in the Shark River estuary, the main drainage of Everglades National Park, Florida. Non-conservative mixing of fDOM along the salinity gradient suggested mangrove inputs accounted for 6% of the total DOC pool. Average changes in fDOM concentrations through individual tidal cycles ranged from less than 10% to greater than 50% and multi-day trends greater than 100% change in fDOM concentration were observed. Salinity and water level both inversely correlated to fDOM at sub-hourly and daily resolutions, while freshwater controls via precipitation and water management were observed at diel to monthly time-scales. In particular, the role of water management in rapidly shifting estuarine salinity gradients and DOC export regimes at sub-weekly time-scales was evident. Additionally, sub-hourly spikes in ebb-tide fDOM indicated rapid exchange of DOC between mangrove sediments and the river channel. DOC fluxes calculated from high-resolution fDOM measurements were compared to monthly DOC measurements with high-resolution fluxes considerably improving accuracy of fluxes (thereby constraining carbon budgets). This study provides a better understanding of short-term DOC dynamics and associated hydrological drivers and indicates the importance of high-frequency measurements to accurately constraining coastal carbon processes and budgets, particularly in coastal systems increasingly altered by hydrologic restoration and climate change.